2017
DOI: 10.1142/s0578563417500048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Macro-Roughness Element on Tsunami Wave Amplification, Pressures, and Loads: Physical Model and Comparison to Japanese and US Design Equations

Abstract: Experiments were conducted at a 1:20 length scale in a large tsunami flume to measure wave evolution and pressures on and around structural elements. The water surface profiles of waves propagating across a bare beach were compared with those recorded in front of an onshore obstacle representing an urban macro-roughness element. The addition of a structure significantly changed the water surface profile for broken waves: the water surface amplification in the presence of a macro-roughness element reached seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This finding is proven by Tomiczek et al (2016b), who showed the HyTOFU could produce both bore and solitary waves within the targeted water surface elevation when conducted on a flat topography with distance varied from the coastline to x = 24.3 m. In this study, this observation provides a complementary result that the water surface elevation from bore and solitary waves could not reach the targeted elevation on the WG9 benchmark location since it was located higher than the sea level elevation. Within this condition, the water propagation from offshore to onshore experienced an interaction process with the topography elevation and the urban coastal infrastructure to reach the targeted elevation.…”
Section: ) the Incoming Tsunami Waves Propagate On Land With No Obstmentioning
confidence: 50%
See 1 more Smart Citation
“…This finding is proven by Tomiczek et al (2016b), who showed the HyTOFU could produce both bore and solitary waves within the targeted water surface elevation when conducted on a flat topography with distance varied from the coastline to x = 24.3 m. In this study, this observation provides a complementary result that the water surface elevation from bore and solitary waves could not reach the targeted elevation on the WG9 benchmark location since it was located higher than the sea level elevation. Within this condition, the water propagation from offshore to onshore experienced an interaction process with the topography elevation and the urban coastal infrastructure to reach the targeted elevation.…”
Section: ) the Incoming Tsunami Waves Propagate On Land With No Obstmentioning
confidence: 50%
“…The Japan Cabinet Office (JCO) provides simple equations to estimate the maximum pressures and load caused by a tsunami based on the Asakura formula. According to Tomiczek et al (2016b), the design equation proposed by the JCO/Task Committee under the Japanese Cabinet Office (2005) is based on a series of laboratory experiments performed by Asakura et al (2002) on 2D scale models. From these experiments, Asakura et al empirically assumed the maximum tsunami loading to be a triangular distribution with base pressure, P max , equal to three times the hydrostatic pressure as follows:…”
Section: Pressure Acting On Structuresmentioning
confidence: 99%
“…Tomiczek et al (2016) performed physical modelling considering the tsunami onshore propagation and the effect of shielding by an array of structures that could reduce the wave-induced forces. The research was extended by Tomiczek et al (2017), where the experimental resulting forces were compared with the US and Japanese design equations. The comparison showed that generally the design codes' total force estimations over and under-estimated the test results for nonbreaking and breaking waves, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have indicated that the shielding effect, which significantly reduces tsunami loads on a structure landward of another one, can be important (Kakinuma et al 2011;Tomiczek et al 2017;Robertson and Mohamed 2009;Winter et al, 2020;Wüthrich et al, 2018), limited studies have clarified the extent of the area where the shielding effect can work effectively. Thus, it is important to understand further how the spatial distribution of tsunamis flowing through various building configurations changes over time using the PIV technique.…”
Section: Introductionmentioning
confidence: 99%